Effect of Permafrost Thaw Slumps on Benthic Invertebrates and on Concentrations of Persistent Organic Pollutants in Lakes of the Mackenzie Delta Uplands, NT - Rebecca, D'Onofrio (Université d'Ottawa / University of Ottawa, 2014)
Permafrost thaw slumping along lakeshores in lakes of the Mackenzie Delta Uplands, NT is known to alter water chemistry significantly. Its impact on benthic communities and persistent organic pollutant (POP) behaviour in lakes is not known. Benthic invertebrate communities responded to slumps through changes to community composition and size spectra. Larger taxa tended to dominate in lakes with slumps. Variability in biomass size spectra was related to total dissolved nitrogen concentration and slump size. Concentrations of POPs in Gammarus were negatively correlated with total phosphorus and positively correlated with the percentage of the catchment slumped. Lakes with slumps generally had higher mean concentrations of POPs in Gammarus (ex. ΣPCBsDisturbed = 27.54 ng/g lipid, ΣPCBsUndisturbed = 16.97 ng/g lipid; ΣDDT Disturbed =18.47 ng/g lipid and ΣDDTUndisturbed =10.86 ng/g lipid). Benthic invertebrate biomass was also negatively correlated with concentrations of contaminants in Gammarus, supporting the biomass dilution hypothesis. Thaw slumps have large enough impacts on the physico-chemical characteristics of lakes that they alter benthic invertebrate community composition and size-structure, and contaminant concentrations in Gammarus.
Keywords: Permafrost thaw slump; Persistent Organic Pollutant; POP; Size Spectra; Benthic macroinvertebrate